2011
DOI: 10.3389/fneur.2011.00070
|View full text |Cite
|
Sign up to set email alerts
|

Functional anatomy of non-REM sleep

Abstract: The state of non-REM sleep (NREM), or slow wave sleep, is associated with a synchronized EEG pattern in which sleep spindles and/or K complexes and high-voltage slow wave activity (SWA) can be recorded over the entire cortical surface. In humans, NREM is subdivided into stages 2 and 3–4 (presently named N3) depending on the proportions of each of these polygraphic events. NREM is necessary for normal physical and intellectual performance and behavior. An overview of the brain structures involved in NREM genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 108 publications
(182 reference statements)
2
57
0
Order By: Relevance
“…This neglect is intriguing, because malfunction of the cerebellum does not only impair motor control and motor memory formation [6][7][8], but it may also lead to changes in the sleep-wake cycle [9,10] and even cause sleep disorders [11]. Furthermore, decades of behavioral and physiological research has shown the positive impact of sleep on episodic memory formation.…”
Section: The Cerebellum Is Still An 'Uncharted Land' In Sleep Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…This neglect is intriguing, because malfunction of the cerebellum does not only impair motor control and motor memory formation [6][7][8], but it may also lead to changes in the sleep-wake cycle [9,10] and even cause sleep disorders [11]. Furthermore, decades of behavioral and physiological research has shown the positive impact of sleep on episodic memory formation.…”
Section: The Cerebellum Is Still An 'Uncharted Land' In Sleep Researchmentioning
confidence: 99%
“…K-complexes are single slow waves occurring typically in NREM2. Spindles are short bursts of activity at a frequency of [10][11][12][13][14][15]. More continuous slow waves occur in what is considered deep sleep, NREM3, or SWS [12].…”
Section: Nrem-dependent Cerebellar Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…10,13,14,18,19 It must be noted, though, that studies using polysomnography in patients with SCA 3 have failed to show a significantly higher incidence of sleep disordered breathing and a significantly different average respiratory disturbance index (RDI) or average apnea hypopnea index (AHI) in these patients as compared to healthy controls. 9,10 The cerebellum plays an underappreciated role in the sleep wake cycle 20 and breathing, [21][22][23] and its involvement in patients with SCA might lead to some of their sleep and respiratory problems.…”
Section: Discussionmentioning
confidence: 99%
“…Bazil (2,4). Determining the cause of a seizure in an adult patient can be difficult, and many adults presenting with their first seizure do not have an identifiable cause (5, 6).…”
Section: Discussionmentioning
confidence: 99%